Agonis Reseptor Glucagon-Like Peptide-1 (GLP-1) sebagai Terapi Neuroprotektif Baru pada Penyakit Parkinson: Dari Mekanisme Molekuler hingga Perspektif Klinis - Arief Gunawan Darmanto (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2026)
Abstract—Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by the loss of dopaminergic neurons in the substantia nigra and the formation of Lewy bodies, which cause motor and non-motor symptoms. Current therapies, such as levodopa, are only symptomatic and have not yet been able to slow the process of neurodegeneration. Recent research indicates a close association between PD and type 2 diabetes mellitus through mechanisms involving insulin resistance, oxidative stress, chronic inflammation, and mitochondrial dysfunction. This opens up opportunities for the use of antidiabetic drugs, particularly glucagon-like peptide-1 (GLP-1) receptor agonists, as potential neuroprotective therapies. GLP-1 receptor agonists are known to work by activating signaling pathways to enhance neurogenesis, strengthen the antioxidant system, suppress inflammatory pathways, and inhibit apoptosis. Preclinical and clinical studies demonstrate the neuroprotective potential of GLP-1 agonists in PD, although their efficacy requires further confirmation due to inconsistent clinical trial results. Nevertheless, GLP-1 receptor agonists have offered a promising new therapeutic approach for modifying the course of the disease. Further research is needed to optimize drug delivery to the brain, identify the most responsive patient subgroups, and assess their long-term safety and efficacy. Keywords: parkinson's disease, GLP-1 agonists, neuroprotection, oxidative stress, inflammation, apoptosis, neurogenesis Abstrak—Penyakit Parkinson (PD) merupakan gangguan neurodegeneratif progresif yang ditandai oleh kehilangan neuron dopaminergik di substantia nigra dan pembentukan Lewy bodies, yang menyebabkan gangguan motorik dan non-motorik. Terapi yang ada saat ini, seperti levodopa, hanya bersifat simptomatik dan belum mampu memperlambat proses neurodegenerasi. Penelitian terkini menunjukkan adanya hubungan erat antara PD dan diabetes melitus tipe 2 melalui mekanisme resistensi insulin, stres oksidatif, inflamasi kronis, dan disfungsi mitokondria. Hal ini membuka peluang pemanfaatan obat antidiabetes, khususnya agonis reseptor glucagon-like peptide-1 (GLP-1), sebagai terapi potensial yang bersifat neuroprotektif. Agonis reseptor GLP-1 diketahui bekerja melalui aktivasi jalur pensinyalan untuk meningkatkan neurogenesis, memperkuat sistem antioksidan, menekan jalur inflamasi, serta penghambatan apoptosis. Studi preklinis dan klinis menunjukkan potensi neuroprotektif agonis GLP-1 pada PD, meskipun efektivitasnya masih memerlukan konfirmasi lebih lanjut karena hasil uji klinis yang belum konsisten. Bagaimanapun juga, agonis reseptor GLP-1 telah menawarkan pendekatan terapeutik baru yang menjanjikan dalam memodifikasi perjalanan penyakit. Penelitian lanjutan diperlukan untuk mengoptimalkan penghantaran obat ke otak, mengidentifikasi subkelompok pasien yang paling responsif, serta menilai keamanan dan efektivitas jangka panjangnya. Kata kunci: penyakit parkinson, agonis GLP-1, neuroproteksi, stres oksidatif, inflamasi, apoptosis, neurogenesis